2011
DOI: 10.1016/j.ntt.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescent executive functioning, intrauterine exposures and own drug use

Abstract: Individual differences in adolescents' executive functioning are often attributed either to intrauterine substance exposure or to adolescents' own substance use, but both predictors typically have not been evaluated simultaneously in the same study. This prospective study evaluated whether intrauterine drug exposures, the adolescents' own substance use, and/or their potential interactions are related to poorer executive functioning after controlling for important contextual variables. Analyses were based on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 108 publications
(164 reference statements)
1
25
3
Order By: Relevance
“…Although the reason for this counter-intuitive finding is not known, similar paradoxical effects were found in prior research with this cohort at different ages [13,47,113]. Some have suggested that, in the context of prenatal exposure to other substances, prenatal tobacco exposure may serve a protective function for some aspects of neuropsychological functioning, or may reflect gene-environment transactions not assessed in the present study [39,53,57,114]. …”
Section: Discussionsupporting
confidence: 60%
“…Although the reason for this counter-intuitive finding is not known, similar paradoxical effects were found in prior research with this cohort at different ages [13,47,113]. Some have suggested that, in the context of prenatal exposure to other substances, prenatal tobacco exposure may serve a protective function for some aspects of neuropsychological functioning, or may reflect gene-environment transactions not assessed in the present study [39,53,57,114]. …”
Section: Discussionsupporting
confidence: 60%
“…48 A third found no relations with working memory or inhibitory control, but the PCE group improved at a slower rate and had marginally lower scores than the NCE group on incidental memory tasks. 36 Another study found that the PCE group demonstrated poorer performance on 2 memory tasks compared with the NCE group.…”
Section: Cognition/schoolmentioning
confidence: 88%
“…Six of the 8 studies examined prenatal tobacco, alcohol, and marijuana exposure [35][36][37]45,48,49 ; 1 included prenatal tobacco and alcohol only. 24 Five measured exposures as any versus none (Table 5).…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations